Investigating the lyrical literature’s content-related apendixes and indicators in The Holy Defense Poems and Resistance Literature - Tabatabaee Ghomshe, Farzaneh (2020)
Iran's lyrical literature and its elements have long attracted the attention of Iranian literary poets, such that they have manifested themselves in most works of art, even on epic and theosophical themes, as well as in literature. of resistance and constancy. The holy defense poems are representations of the thought and feeling of Iran at a time in its history whose emotional and affective aspects are of great cultural importance. In this sense, the present study attempts to investigate the indicators of lyrical literature in the resistance literature poems of three prominent poets in this area, namely, Ali Mo’allem Damghani, Qaisar Aminpour and Ali Reza Qazveh. The study method of this research is descriptive-analytical and the data collection method is bibliographic research based on content analysis. The lyrical elements of the envisioned poems are love, patriotism, waiting, thanatopsis and martyrdom, and attention to the emotions and feelings of the holy defense poets in later years, among others. The results and findings of the study meant that the elements of the lyrical literature present aspects of the slogan and that they have been notably manifested in the sacred defense literature in the area of the compositions of the studied poets and also that these three poets have been able to exhibit many manifestations of poetic sentiment in his poems about the imposed war.